Analisis Kesiapan Guru Sekolah Dasar dalam Implementasi Kurikulum Merdeka - Heryahya, Andang; Herawati, Endang Sri Budi; Susandi, Ardi Dwi; Zulaiha, Fanni (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The aims of this study were (1) to describe the understanding of elementary school teachers in Cirebon City about independent curriculum policies, (2) to describe the readiness of elementary school teachers in Cirebon City to formulate learning objectives for the Pancasila profile, (3) to describe the readiness of elementary school teachers in Cirebon City to implement learning 21st century, and (4) describes the readiness of elementary school teachers in Cirebon City in identifying students' self-potential. This study uses a survey research design and needs assessment. The population of this study were public elementary school teachers in Cirebon City. There are 128 public elementary schools in Cirebon city, so the population of this study is 768 teachers. The sample was determined using simple random sampling technique. Based on Issac Michael's table with a 5% sampling error, a total sample of 238 teachers was obtained. The data collection technique uses a questionnaire instrument given to teachers and interviews with several key informants. The key informants in this study were the Head of Basic Education in Cirebon City and several school principals. The results of this study are (1) public elementary school teachers in Cirebon City understand the essence of the Independent Curriculum policy, (2) public elementary school teachers in Cirebon city understand in formulating learning objectives for Pancasila student profiles, (3) public elementary school teachers in the city Cirebon is ready to implement 21st century learning, (4) Public Elementary School teachers in Cirebon City are ready to identify various kinds of potential in students. Based on these results, it can be concluded that SD Negri teachers in Cirebon City are ready to implement the independent curriculum in classroom learning. Keyword: Analysis, Elementary School Teacher Readiness, Implementation of the Independent Curriculum